The Awareness levels of science and technology teacher candidates towards ecological footprint - Yıldız, Emre; Selvi, Mahmet (Journal of Turkish Science Education, 2015)
The aim of this study was to investigate and evaluate the ecological footprint awareness levels of science and technology teacher candidates. This research was performed in 361 science and technology teacher candidates, who were in Science Education Department of Gazi Education Facultyof Gazi University in the spring semester of 2013-2014. The research was carried out using a crosssectional survey model. The variables of this research were gender and grade levels. The data were collected using the Ecological Footprint Awareness Scale. Descriptive statistic techniques,independent samples t-test, and one-way ANOVA were used for data analysis. The results obtained from this study showed that science and technology teacher candidates have the largest footprint in food subscale, and the smallest footprint in energy subscale. The ecological footprint awareness levels of female science and technology teacher candidates were found significantly higher than those of male science and technology teacher candidates. The ecological footprint awareness of science and technology teacher candidates was observed significantly higher than that of freshmen science and technology teacher candidates.
Keywords: Ecological Footprint; Environmental Education; Science and Technology Education; Sustainable Life